Planejamento, síntese e avaliação fotoprotetora de novos compostos híbridos derivados do resveratrol, cinamatos e avobenzona planejados como filtros solares - Reis, Juliana Santana [UNESP] (2014)
The exposure to ultraviolet radiation is the mainly factor to develop skin cancer and photoaging. This work aimed to obtain new sunscreens with enhance abilities to protect against UVA and UVB radiation associated to antioxidant properties, obtained by molecular hybridization strategy among existing filters (avobenzone and methoxycinnamate) and natural products (resveratrol and ferulic acid). Eight new compounds were synthesized, isolated and characterized by molecular hybridization: (E)-4-hydroxy-N'-(4-hydroxybenzylidene)benzohydrazide (molécula I), (E)-N'-(3,5-dihydroxybenzylidene)-4-hydroxybenzohydrazide (molécula II), (E)-4-(tert-butyl)-N'-(3,5-dihydroxybenzylidene)benzohydrazide (molécula III), (E)-4-(tert-butyl)-N'-(4-hydroxybenzylidene)benzohydrazide (molécula IV), (E)-4-hydroxy-N'-((E)-3-(4-methoxyphenyl)allylidene)benzohydrazide (molécula V), (E)-4-(tert-butyl)-N'-((E)-3-(4-methoxyphenyl)allylidene)benzohydrazide (molécula VI), (E)-4-hydroxy-N'-((E)-3-(4-hydroxy-3-methoxyphenyl)allylidene)benzohydrazide (molécula VII) and (E)-4-(tert-butyl)-N'-((E)-3-(4-hydroxy-3-methoxyphenyl)allylidene)benzohydrazide (molécula VIII). Compound VIII was presented as the most thermostable, showing decomposition temperature above 295°C. Compounds I, IV, VII and VIII presented more antioxidant activity than the other compounds analysed. The compounds VII and VIII were similar to ferulic acid, t-resveratrol and ascorbic acid. Compounds I, IV, V, VI, VII and VIII had abilities to protect against UVA radiation, and all of these products were similar to t-resveratrol pattern. The VI molecule had the highest photoprotection activity against UVA radiation, and it was more effective than t-resveratrol pattern. The II and III compounds were classified as UVB filters and they were more effectiveness than t-resveratrol. Compounds I, III, V and VII showed inhibitory ability for the enzyme tyrosinase, respectively, ...